2007
DOI: 10.1590/s1519-69842007000400026
|View full text |Cite
|
Sign up to set email alerts
|

Seminavis atlantica Garcia, a new psammic diatom (Bacillariophyceae) from southern Brazilian sandy beaches

Abstract: The paper presents the description of Seminavis atlantica Garcia, a psammic marine diatom from dissipative sandy beaches from southern Brazil. It is characterized by its convex linear dorsal margin (37 to 50% of its length is in a straight line), linear ventral margin and raphe located very close to the ventral margin. Its morphology is compared to similar species such as Amphora clevei Grunow, Amphora angusta (Greg.) Cleve var. orientalis Allem, Amphora ventricosa Gregory and Amphora eulesteinii Grunow.Keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…After the initial description of Seminavis, eighteen species were combined and discovered in this genus occurring in marine and brackish waters (round et al 1990;danielidis & Mann 2002danielidis & Mann , 2003Cox & reid 2004;danielidis et al 2006;garCia 2007;WaChniCKa & gaiser 2007;WiTKoWsKi et al 2000). Up to now, the species recorded from Brazil are S. atlantica garCia by garCia (2007) and souza- MosiMann et al (2011), S. robusta danielidis et Mann (as Amphora angusta gregory and Amphora angusta var.…”
Section: Introductionmentioning
confidence: 99%
“…After the initial description of Seminavis, eighteen species were combined and discovered in this genus occurring in marine and brackish waters (round et al 1990;danielidis & Mann 2002danielidis & Mann , 2003Cox & reid 2004;danielidis et al 2006;garCia 2007;WaChniCKa & gaiser 2007;WiTKoWsKi et al 2000). Up to now, the species recorded from Brazil are S. atlantica garCia by garCia (2007) and souza- MosiMann et al (2011), S. robusta danielidis et Mann (as Amphora angusta gregory and Amphora angusta var.…”
Section: Introductionmentioning
confidence: 99%
“…Many acids like formic acid, butyric acid, anacardic acid, acetic acid and hydrochloric acid are found effective in controlling avian coccidiosis (Garcia, 2007), (Zamanet al,2012). A work by Garcia (Garcia, 2007) reported that formic acid has positive effects on growth of villi such as increase in height of villi, depth of crypt and surface area of villi in broiler chickens experimentally challenged with E. tenella. Organic acids like acetic acid have also been reported to have anti-coccidial effects.…”
Section: (C) Alternative Control Measures (1) Acidmentioning
confidence: 99%
“…Most of these records have no sufficiently morphometrical and photographical data to confirm the identifications, except in Sylvestre et al (2001), Garcia (2007), Garcia and Souza (2008), Talgatti (2011), Souza-Mosimann et al (2011) and Bes et al (2012).…”
Section: Introductionmentioning
confidence: 98%
“…Seminavis was included in Naviculales, because of raphe and areolae structures more similar to members of this order, rather than valve strongly dorsiventral shared with Amphora. Thereafter, a number of papers have shown the morphology of former Amphora species, with transfers and new propositions to the genus Seminavis (Garcia-Baptista, 1993;Danielidis and Mann, 2002;Danielidis et al, 2006;Garcia, 2007;Wachnicka and Gaiser, 2007).…”
Section: Introductionmentioning
confidence: 99%